1983
DOI: 10.1007/bf01914676
|View full text |Cite
|
Sign up to set email alerts
|

Some experimental aspects of the determination of kinetic parameters by means of temperature-programmed desorption

Abstract: The process of desorption of a gas from a catalyst surface, especially when temperatureprogrammed, can be affected by the occurrence of other chemical or physical processes.On the basis of a simple method of analysis, which makes possible the examination of definite fractional areas of a peak, and therefore the examination of definite ranges of surface coverage during desorption, this paper examines two experimental cases of temperature-programmed desorption, relating to propylene metathesis on the practical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 7 publications
1
7
0
Order By: Relevance
“…4,5 Spinicci et al performed propylene temperature-programmed desorption (TPD) and observed that propylene desorption follows second-order kinetics from supported WO x /SiO 2 catalysts. 6 This TPD study, however, monitored only desorption of propylene, and no information about the desorption of 2-butene or ethylene metathesis reaction products was provided.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…4,5 Spinicci et al performed propylene temperature-programmed desorption (TPD) and observed that propylene desorption follows second-order kinetics from supported WO x /SiO 2 catalysts. 6 This TPD study, however, monitored only desorption of propylene, and no information about the desorption of 2-butene or ethylene metathesis reaction products was provided.…”
Section: Introductionmentioning
confidence: 99%
“…The current literature of olefin metathesis by supported WO x /SiO 2 catalysts has taken a global view of this reaction and has also reported on phenomenological observations. Most of the reported research has focused on fitting overall reaction rates with kinetic models. Begley et al fitted their kinetic data for a supported 9% WO 3 /SiO 2 catalyst with both second-order Langmuir–Hinshelwood and first-order Eley–Rideal reaction mechanisms and found that the Eley–Rideal model adequately correlated their data . They also concluded that the catalyst surface is saturated at high pressures (300–900 psia and 300–500 °C) and that the reaction rate is controlled by the rate of adsorption of olefin on the surface sites .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Spinicci et al concluded that desorption of propylene from supported ReO x /Al 2 O 3 catalysts follows second-order kinetics with temperature-programmed desorption (TPD) studies. 10 Some kinetic studies suggested that olefin metathesis proceeds via the Langmuir−Hinshelwood kinetic model, 8,11,12 but Kapteijn et al considered the L-H model inadequate and developed a first-order kinetic model based on intermediate carbene species (ReCH 2 and ReCHCH 3 ) with product desorption being the rate-determining step. 13 This mechanism is more in line with Chauvin's metallacyclobutane mechanism that was proposed for homogeneous and supported organometallic catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…In the presence of gasphase C This bimolecular reaction involving recombination of surface intermediates was earlier proposed by Spinicci et al from TPD studies of propylene desorption. 10 The bimolecular recombination of surface intermediates cannot be dominant at elevated temperatures, since it would give a reaction order of 1 with respect to propylene partial pressure, which is much lower than the measured reaction order of ∼1.8. The steady-state apparent reaction order of slightly less than 2, ∼1.8, may reflect the partial contribution of this surface bimolecular reaction pathway at elevated temperatures.…”
Section: Introductionmentioning
confidence: 99%